Manifestacions folclóricas del distrito de Contumazá, región Cajamarca, para impulsar el desarrollo del turismo cultural. - González Vilchez, Johanna (2013)
The Tourism Research report called: "Folkloric manifestations of Contumazá district, Cajamarca region, to promote cultural tourism development", located in Contumazá district, Contumazá Province, Cajamarca region, has been designed to determine the folkloric manifestations which development of cultural tourism in this district. _x000D_ Contumazá district has a large number of popular beliefs expressed in tales and legends, the most representative are the tales of Uncle Lino and the legend of the Kuam y Tatntarica, these have a cultural value generated Contumaza community transmitted from generation to generation , giving it attractiveness to the people; indeed capable of promoting the development of cultural tourism. _x000D_ The village retains Contumazá traditional festivals, in which they highlight the music and dances representing this community so we within the most mentioned to the Feast of San Mateo, Easter and Carnival, the cultural value of these resources is manifested in contumacino people's identity with his own, a situation favorable for the development of cultural tourism. _x000D_ The food and crafts are also important folklore Contumazá within gastronomy highlight the "new love", apple cider and fresh cheese with honey and crafts within the tissues have industrial yarn and crochet hats reed and palm, these resources denote a cultural value expressed by the residents of Contumazá, a fact that allows the development of Cultural Tourism.